Efficacy of High-Dose Amoxicillin-Clavulanate against Experimental Respiratory Tract Infections Caused by Strains of Streptococcus pneumoniae - Woodnutt, Gary (American Society for Microbiology, 1999)
The purpose of the present investigation was to determine if the efficacy of amoxicillin-clavulanate against penicillin-resistant Streptococcus pneumoniae could be improved by increasing the pediatric amoxicillin unit dose (90 versus 45 mg/kg of body weight/day) while maintaining the clavulanate unit dose at 6.4 mg/kg/day. A rat pneumonia model was used. In that model approximately 6 log(10) CFU of one of four strains of S. pneumoniae (amoxicillin MICs, 2 μg/ml [one strain], 4 μg/ml [two strains], and 8 μg/ml [one strain]) were instilled into the bronchi of rats. Amoxicillin-clavulanate was given by computer-controlled intravenous infusion to approximate the concentrations achieved in the plasma of children following the administration of oral doses of 45/6.4 mg/kg/day or 90/6.4 mg/kg/g/day divided every 12 h or saline as a control for a total of 3 days. Infusions continued for 3 days, and 2 h after the cessation of infusion, bacterial numbers in the lungs were significantly reduced by the 90/6.4-mg/kg/day equivalent dosage for strains for which amoxicillin MICs were 2 or 4 μg/ml. The 45/6.4-mg/kg/day equivalent dosage was fully effective only against the strain for which the amoxicillin MIC was 2 μg/ml and had marginal efficacy against one of the two strains for which amoxicillin MICs were 4 μg/ml. The bacterial load for the strain for which the amoxicillin MIC was 8 μg/ml was not reduced with either dosage. These data demonstrate that regimens which achieved concentrations in plasma above the MIC for at least 34% of a 24-h dosing period resulted in significant reductions in the number of viable bacteria, indicating that the efficacy of amoxicillin-clavulanate can be extended to include efficacy against less susceptible strains of S. pneumoniae by increasing the amoxicillin dose.